Efektivitas Media Lagu Berjudul â€œStruktur Suratâ€ Karya Dwi Fitriani dan Pendekatan Culturally Responsive Teaching (CRT) dalam Meningkatkan Kemampuan Menulis Surat Pribadi Peserta Didik Kelas VII.2 di SMP Negeri 11 Palembang - Firanata, Aldy; H, Hetilaniar; Yulita, Nyimas Laili; Srikandi, Intan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to improve the ability of VII.2 students at SMP Negeri 11 Palembang to write personal letters by using song media and the Culturally Responsive Teaching (CRT) approach. This research was conducted using a classroom action research method with a qualitative approach. The data was collected through observation, interviews, and tests. The results showed that the use of song media and the CRT approach was effective in improving students' ability to write personal letters. This was indicated by the percentage of students' scores exceeding the KKM in writing personal letters, starting from 53.55% in cycle I and increasing to 85.43% in cycle II. Based on the results of interviews with students, it was revealed that the use of songs and the CRT approach helped them improve their ability to write personal letters more significantly.